2014
DOI: 10.1149/2.0941410jes
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Density Calendered Si Alloy/Graphite Anodes

Abstract: The effect of calendering and adding graphites of different particle sizes to composite electrodes comprising Si alloy particles was evaluated. It was found that calendered alloy coatings containing graphite results in increased cycling performance, reduced volume expansion and increased energy density compared to a pure alloy coating. Such high energy density, low volume expansion coatings are expected to be practical for implementation in high energy density Li-ion cells.The development of high energy Li-ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
127
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(137 citation statements)
references
References 31 publications
5
127
1
4
Order By: Relevance
“…9 Such coatings are In a previous study of sputtered Ni-Si thin films, we showed that the lithiation voltage is depressed with increasing Ni content, while the delithiation voltage remains unchanged.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…9 Such coatings are In a previous study of sputtered Ni-Si thin films, we showed that the lithiation voltage is depressed with increasing Ni content, while the delithiation voltage remains unchanged.…”
Section: Resultsmentioning
confidence: 81%
“…2,7 In a recently published article, it was shown that the formation of Li 15 Si 4 is avoided during cycling of 3 M V6 active/inactive Si alloy, even at lower cutoff voltages as low as a 5 mV. 8,9 The absence of Li 15 Si 4 formation has been shown to result in improved cycling performance in alloys. 3 Si-TM alloys (TM = a transition metal) have been extensively studied as negative electrodes.…”
mentioning
confidence: 99%
“…1,2 In contrast to conventional intercalation anode materials, such as graphite (LiC 6 , 372 mAh g −1 , 890 Ah L −1 ), the specific capacity of silicon alloy electrodes is significantly higher (Li 15 Si 4 , 3579 mAh g −1 , 2194 Ah L −1 ). 3 Nonetheless, commercialization of silicon-based electrodes is still hampered because of two major challenges: 4 (i) Large volume expansions up to 280% upon repeated (de-)lithiation of silicon particles deteriorate the electrode integrity, thus causing isolation of active material.…”
mentioning
confidence: 99%
“…8 In the course of this, SEI-forming additives in the electrolyte, e.g., FEC, are depleted, which was shown to result in a significant increase in cell polarization and a concomitant rapid capacity drop. 8,11 Various strategies have been proposed to overcome the detrimental effects associated with the volume expansion during (de-)lithiation of silicon and to reduce concomitant irreversible capacity losses, including preparation of silicon thin-films with a significantly reduced silicon/electrolyte interface, 6,[12][13][14] Si-Al-Fe active/inactive alloy electrodes that reduce the volume expansion of the active phase, 5,15,16 and design of nanostructured silicon materials with carbonaceous compounds, such as graphite, to improve the electrical conductivity within the electrode and to better accommodate the volume expansion of silicon. [17][18][19][20] Although the surface area per capacity usually increases for nanostructured silicon materials with decreasing diameter, 21 which leads to a higher first cycle irreversible capacity loss, silicon nanowires offer the advantage of a smaller relative surface area change upon (de-)lithiation and in addition usually reveal less morphological changes, due to a reduced mechanical stress within the materials.…”
mentioning
confidence: 99%
“…2 To overcome the issues associated with Li 15 Si 4 phase formation and volume expansion during cycling, researchers have demonstrated high cycle life in Li cells by using Si in the form of nanoparticles, 3,4 nanowires, 5,6 nanopillars, 7,8 thin films, 9,10 and in alloys with inactive or active phases. 11,12 These studies have reported various threshold sizes for nanoparticles (150 nm), 3,4 nanowires (300 nm), 13 and amorphous thin films (2.5 μm), 14 below which Li 15 Si 4 formation does not occur. These results imply that the Li 15 Si 4 phase may be a consequence of particle aggregation; however, the variance in threshold size among Si morphologies raises questions.…”
mentioning
confidence: 99%